Microbiological quality of white-brined cheeses: A review - Bintsis, Thomas; Papademas, Photis (My University, 2002)
White-brined cheeses are widely produced in the North-east Mediterranean area and the Balkans. Traditionally, they were manufactured as artisanal cheeses, and nowadays they are manufactured on an industrial scale, and rigorous control of the production and maturation processes is essential. Aspects of the microbiology of white-brined cheeses and their significance with respect to the quality and safety of the final products are discussed in this review
Keywords: Domiati; Feta; Halloumi; Microbiology; White-brined cheeses